THE FRIENDSHIP CONSTRUCTION IN MARY AND MAX FILM SCRIPT: A NARRATIVE ANALYSIS - Putri, Kristanti Dwi (2013)
Titled The Friendship Construction in Mary and Max film script: a Narrative Analysis, the present research aims to investigate how focalization affects the theme of friendship in Mary and Max film script. This research applied Gerard Genette's (1980) narratology as a tool to answer the aim of the research by employing qualitative descriptive method. Based on the analysis, the present research found that the theme of friendship in Mary and Max film script is affected by zero focalization and internal focalization. This research concludes that through the use of zero focalization and internal focalization, the story of Mary and Max successfully captures a portrait of sincere friendship which accentuates a disabled person as a good character. Keywords: narrative, focalization, Genette, narratology, friendship Berjudul The Friendship Construction in Mary and Max film script: a Narrative Analysis, penelitian ini bertujuan untuk mengetahui bagaimana fokalisasi mempengaruhi tema persahabatan dalam naskah film Mary and Max. Penelitian ini mengaplikasikan teori naratologi dari Gerard Genette (1980) sebagai alat untuk menjawab tujuan penelitian dengan menggunakan metode kualitatif deskriptif. Berdasarkan analisis, penelitian ini menemukan bahwa tema persahabatan dalam naskah film Mary and Max dipengaruhi oleh fokalisasi nol dan fokalisasi internal. Penelitian ini menyimpulkan bahwa melalui penggunaan fokalisasi nol dan fokalisasi internal, cerita Mary and Max berhasil memberikan gambaran tentang persahabatan yang tulus, yang menekankan seorang penyandang cacat sebagai karakter yang baik. Kata kunci: naratif, fokalisasi, Genette, naratologi, persahabatan